Pelaksanaan Badan Usaha Milik Desa (Studi BUMDes Desa Gulingan Kabupaten Badung) - Putu Ferdiana Putra; Desak Gede Dwi Arini; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2020)
Village-Owned Enterprises (BUMDes) are village business entities that are managed by the community and village government in an effort to strengthen the village economy and are formed based on the needs and potential of the village. One of the villages in the Sub-district of Badung is Gulingan Mengwi. It already has an enterprise named BUMDes Samkriya Werdhi Guna. This study examines two issues: the regulation of Village Owned Enterprises of Samkriya Werdhi Guna to bear a crucial role in the efforts to increase the Village Original Revenue of Mengingan Gulingan and the implementation of BUMDes based on the Regional Regulation of Badung Regency No. 1 of 2015 concerning the Establishment and Management of Village-Owned Enterprises in Gulingan Mengwi Village. To achieve the objectives, empirical legal research method was used. The results of the study showed that the Regulation of the Samkriya Werdhi Guna Village Owned Enterprise had an important role in the effort to increase the Original Revenue of the Gulingan Mengwi Village to support the development program in the village. The implementation of the BUMDes in conjunction with the Regional Regulation of Badung Regency No. 1 of 2015 concerning the Establishment and Management of Village-Owned Enterprises in the the Mengwi Mengingan Village is in accordance with the principles of the Statutory Regulations. In addition, the participation of the Government of Badung Regency is also ideal for developing the BUMDes, especially in BUMDes of the Samkriya Werdhi Guna of Gulingan Mengwi Village.